Atmospheric palaeo-CO2 estimates based on the carbon isotope and stomatal data of Cheirolepidiaceae from the Lower Cretaceous of the Jiuquan Basin, Gansu Province. (July 2016) - Du, Baoxia; Sun, Bainian; Zhang, Mingzhen; Yang, Guolin; Xing, Lantian; Tang, Fenjun; Bai, Yanxia
Abstract: The stable carbon isotope compositions and the stomatal parameters (stomatal density and stomatal index) of four Cheirolepidiaceae species, Brachyphyllum ningxiaensis, Brachyphyllum obtusum, Pseudofrenelopsis dalatzensis and Pseudofrenelopsis gansuensis, were analyzed to recover the late Early Cretaceous atmospheric CO2 levels. The fossil plants were collected from 5 consecutive sedimentary members of the uppermost Zhonggou Formation. Based on the stomatal data, the estimated palaeo-atmospheric CO2 concentrations in the Jiuquan Basin during the late Early Cretaceous were 1060–882 ppmv based on the carboniferous standardization and were 641–531 ppmv based on the recent standardization; the p CO2 values present at first a decreasing and then an increasing trend within the sedimentary time of the five members. The δ 13 C p values based on the 21 Brachyphyllum specimens showed a large variation, which ranged from −20.98‰ to −25.69‰, with an average of −24.2‰. The values also identified a C3 photosynthetic pathway for the Brachyphyllum specimens. The predicted δ 1 3 C a values varied from −2.1‰ to −6.38‰, with an average of −5.03‰. These two proxies were irregular within the different members; therefore, the correlation with the change in atmospheric CO2 concentrations was not significant. Moreover, a water-stressed environment was proposed based on the δ 13 C values of the present fossil plants, a proposal that was also supported by the previous palaeobotanical, palynological and stratigraphical evidence. In the present study, an inconsistent relationship between the stable carbon isotope and the stomata values was apparent, which most likely indicated that the stomata numbers of the plant were more sensitive to the variation in the concentration of the atmospheric CO2, whereas the δ 13 C values were sensitive to the moisture conditions. Highlights: The palaeo- p CO2 was estimated based on 4 Cheirolepidiaceae from Jiuquan Basin. The atmospheric CO2 content was 1060–531 ppmv during the late Early Cretaceous. The δ 13 C p values indicated a water-stressed environment. A non-significant correlation between the δ 13 C a and the p CO2 was proposed.